2011
DOI: 10.3233/wor-2011-1117
|View full text |Cite
|
Sign up to set email alerts
|

Sheltered Employment Centers: Characteristics and users' perception

Abstract: Objective: To know the situation of Sheltered Employment Centers (CEE) in the Autonomous Community of Madrid. Method: A quantitative approach was developed by using a questionnaire which was sent to all the CEE. With this questionnaire we got information about the performance level of CEE. A qualitative approach was developed too by using an interview applied to a representative sample of users. With the interview we got information about users' perception and satisfaction. Participants: 73 centers from 175 (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
1
3
0
2
Order By: Relevance
“…they have the right job match and the right support, supporting the extensive literature on supported employment(Beyer, Jordán De Urríes, & Verdugo, 2010;Cimera & Rusch, 1999;De Urríes et al, 2005).…”
supporting
confidence: 60%
“…they have the right job match and the right support, supporting the extensive literature on supported employment(Beyer, Jordán De Urríes, & Verdugo, 2010;Cimera & Rusch, 1999;De Urríes et al, 2005).…”
supporting
confidence: 60%
“…After reading the full-text of potentially relevant publications ( n = 315) for the entire review, we identified 27 articles that met the inclusion criteria for the present review on qualitative studies. Two mixed-methods studies were excluded because it was not possible to differentiate data obtained with qualitative and quantitative methods [ 41 , 42 ]; a third study was excluded because we could not clearly identify the views reported by PwCDs [ 43 ]. This led to a total of 24 publications included in our review [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…After all, rewards such as salary and other benefits are often mentioned in literature on job satisfaction of people without disabilities (Spector ) and have also been put forward as important for persons with disabilities in relation to their integration in the workplace and their job satisfaction (Wehman ; Lysaght et al . ; Jordán de Urríes & Verdugo ).…”
Section: Discussionmentioning
confidence: 99%